NEWS RECOMMENDER SYSTEM USING HYBRID CONTENT-BASED FILTERING AND COLLABORATIVE FILTERING - Nurjayanto, Bagus Wicaksono; Baizal, Z. K. A. (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2024)
The development of online news services has offered users numerous choices, resulting in information overload. This makes it challenging for users to locate desired news within a spesific timeframe. to adress this, recommender systems have developed to help users discover and select news article.